The ratio of working pressure to resting pressure under compression stockings: Its significance for the improvement of venous perfusion in the legs - Häfner, H. M.; Piche, E.; Jünger, M. (Phlebologie, 2001)
Aim: A variety of medical compression products are available for the treatment of chronic venous insufficiency. Aim of this study was to quantify the acute effects of different compression class 2 (CCL2) stockings on venous hemodynamics. We examined the pressure exerted by the stockings as a biophysical parameter and tested for correlations between it and an improvement in venous hemodynamics. Methods: A total of 42 patients with chronic venous insufficiency in stages C1-4 Ep AS, A14, Ap, PR (CEAP classification) took part in the study. Venous hemodynamics were measured by dynamic strain-gauge plethysmography with and without a variety of different CCL2 compression stockings. At the same time, the pressure exerted by the stockings was measured under static conditions (resting pressure) and under dynamic conditions (working pressure). Results: Each of the CCL2 medical compression stockings tested here brought about a different degree of hemodynamic improvement. The amount by which venous refilling time was lengthened varied from one stocking to the next. Hemodynamic improvement was closely correlated with the ratio of working pressure to resting pressure exerted by the stockings (r = 0.90, p <0.001). Conclusion: The degree of hemodynamic improvement attained depended on the elasticity of the compression stocking, i.e. the ratio of maximum working pressure to resting pressure exerted by the stocking.
Keywords: Chronic venous insufficiency; compression stocking; venous hemodynamics; exerted pressure